Significance of uterine corpus tumor invasion in early-stage cervical cancer. Issue 4 (April 2017) - Matsuo, K.; Machida, H.; Blake, E.A.; Takiuchi, T.; Mikami, M.; Roman, L.D.
Abstract: Objective: To examine characteristics and survival outcomes of women with surgically-treated cervical cancer exhibiting uterine corpus tumor invasion. Methods: We utilized The Surveillance, Epidemiology, and End Results Program to identify cervical cancer patients who underwent hysterectomy between 1973 and 2003. Logistic regression models were used to identify risk factors for uterine corpus tumor invasion on multivariable analysis. Association of uterine corpus tumor invasion and cause-specific survival (CSS) from cervical cancer was examined with Cox proportional hazard regression models on multivariable analysis. Results: We identified 837 (4.9%) cases of uterine corpus invasion and 16, 237 (95.1%) cases of non-invasion. Median follow-up time was 14.0 years. There were 1642 deaths due to cervical cancer. Uterine corpus invasion was independently associated with older age, non-squamous histology, high-grade tumors, large tumor size, and nodal metastasis on multivariable analysis (all, P  < 0.001). On univariable analysis, uterine corpus tumor invasion was significantly associated with decreased CSS compared to the non-invasion (5-year rates, 79.0% versus 94.5%, P  < 0.001). After controlling for other significant prognostic factors, uterine corpus tumor invasion remained an independent prognostic factor for decreased CSS (adjusted-hazard ratio 1.45, 95% confidence interval 1.21–1.74). Among stage T1b cases (n = 6730), uterine corpus tumor invasion remained an independent prognostic factor for decreased CSS (adjusted-hazard ratio 1.95, 95%CI 1.47–2.60). Uterine corpus tumor invasion was significantly associated with decreased CSS in stage T1b1 disease (74.5% versus 90.7%, P  < 0.001) and in stage T1b2 disease (67.0% versus 79.5%, P  = 0.01). Conclusion: Uterine corpus tumor invasion is an independent prognostic factor for decreased survival of women with early-stage cervical cancer.